1989
DOI: 10.1002/1097-0142(19890401)63:7<1437::aid-cncr2820630735>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in soft tissue sarcomas. A multivariate analysis of 109 cases

Abstract: Prognostic factors were evaluated in 109 soft tissue sarcomas of the extremities, walls of the trunk, head, and neck. All lesions were graded according to the systems proposed by the National Cancer Institute (NCI) and the French Federation of Cancer Centers (FNCLCC), and a correlation was found between tumor grade and prognosis. Univariate analysis selected the following variables as unfavorable prognostic factors: invasive tumor margins, extra-compartmental status, deep tumors, tumor diameters over 5 cm, ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(89 citation statements)
references
References 20 publications
6
81
1
1
Order By: Relevance
“…histological grade, size, depth, degree of necrosis etc. (Trojani et al, 1984;Rooser et al, 1988;Ueda et al, 1988;Mandard et al, 1989) [ion or on various treatment modalities (Markhede et al, 1982;Bramwell et al, 1985;Suit et al, 1985). In addition, most of tl in sarcoma patients is difficult to assess reliably these observations have been made on hospital-based or on of the rarity of such tumours, their differing toposelected sub-sets of population-based series.…”
Section: Resultsmentioning
confidence: 99%
“…histological grade, size, depth, degree of necrosis etc. (Trojani et al, 1984;Rooser et al, 1988;Ueda et al, 1988;Mandard et al, 1989) [ion or on various treatment modalities (Markhede et al, 1982;Bramwell et al, 1985;Suit et al, 1985). In addition, most of tl in sarcoma patients is difficult to assess reliably these observations have been made on hospital-based or on of the rarity of such tumours, their differing toposelected sub-sets of population-based series.…”
Section: Resultsmentioning
confidence: 99%
“…Soft tissue sarcomas of the head and neck are uncommon and there is only a small number of reported series (Farr et al, 1981;Littman et al, 1983;Wharam et al, 1984;Greager et al, 1985;Fromm et al, 1986;Harmer et al, 1986;Weber et al, 1986;Tsujimoto et al, 1988;Figueiredo et al, 1988;Freedman et al, 1989;Mandard et al, 1989;Rao et al, 1989;Ruka et al, 1989;Frankenthaler et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Costa et al (1984) demonstrated the effect of extent of necrosis on survival and used it in their grading system. Since then other authors (Mandard et al, 1989;Rooser et al, 1988;Trojani et al, 1984) have, like us, shown it to be an independent prognostic factor. Assessment of the extent of necrosis is the most subjective and difficult of the criteria used in grading (Costa et al, 1984;Trojani et al, 1984 (Mandard et al, 1989;Ueda et al, 1988) and site (Collin et al, 1987;Markhede et al, 1982) is well documented in the literature.…”
Section: Discussionmentioning
confidence: 99%